Influence of Co-Firing PKS (Palm Kernel Shell) with Coal on Boiler Efficiency Combustor Type: Reciprocating Servo Grate - Tratama, Teddy; Aspiyansyah, Aspiyansyah; Harianto, Agus; Budi, Agung Prasetyo (International Journal of Mechanical Engineering Technologies and Applications, 2020)
Biomass fuel, recognized for its renewable and environmentally friendly characteristics, presents an attractive option for energy production. This study explores a co-firing system incorporating palm kernel shell (PKS) and coal as fuel feeds for a boiler, aiming to optimize energy production and reduce gas emissions. The influence of co-firing PKS with coal on fuel feed rate and boiler efficiency was analyzed. Boiler efficiency measurements and calculations were conducted using the indirect method. The fuels were co-fired in various ratios: 65:35, 60:40, 55:45, and 50:50 (PKS). The results show that increasing the coal ratio in the fuel blend reduces the fuel feed rate and increases boiler efficiency. The optimized co-firing ratio of PKS to coal was determined to be 60:40, achieving a maximum boiler efficiency of 55.38%.